Pyrazole Carbohydrazide Derivatives of Pharmaceutical Interest - Luiza Rosaria Sousa Dias; Raquel Rocha Silva Salvador (MDPI AG, 2012)
The main purpose of this paper is to provide an insight into the biological activities of pyrazole derivatives which contain the carbohydrazide moiety.